Serotonin is a gap junction-permeable neuronal tracer in the mouse retina - Szarka, Gergely; Hoffmann, Gyula; Kovács-Öller, Tamás; Völgyi, Béla (Frontiers in Ophthalmology, 2023)
Abstract Gap junctions are dynamically modulated bridges allowing for a transcellular passage of ions and small molecules with a molecular mass of up to 1 kDa, a mechanism utilized for molecular communication purposes by living cells. This same mechanism is also exploited by scientists to reveal the existence of gap junction contacts by the cell-to-cell movement of tracers. However, multiple labeling experiments require the availability of multiple gap junction permeable tracers. To this end we utilized the well-known transient OFF alpha retinal ganglion cell (RGC) coupled array as a model system to study and compare the transjunctional movement of Neurobiotin (NB) and serotonin, a commonly used and a recently identified tracer, respectively. Although, the transjunctional movement of serotonin has been established in cell cultures, here we show it for the first time that serotonin is also a potent tracer in the in vitro tissue. In addition, the serotonin is lighter than the classical gap junction permeable NB thus a comparable or better tracer movement of serotonin was expected. We find that intracellular serotonin injections result in the labeling of the coupled transient OFF alpha RGC array very similar to those of the classical Neurobiotin labeled arrays. Both serotonin and NB injected transient OFF alpha RGCs displayed the well-known pattern with coupled RGCs and a cohort of coupled wide-field amacrine cells (WF-ACs). By using morphological characteristics, we confirm that the serotonin and the NB coupled AC arrays are identical thereby confirming that serotonin is a potent gap junction permeable tracer and can be readily used as an alternative of NB in the in vitro tissue. Moreover, serotonin can be utilized in parallel with other dyes or tracers including NB to perform multiple labels in the same material.